2013
DOI: 10.1002/hep.25749
|View full text |Cite
|
Sign up to set email alerts
|

IL28B polymorphisms predict interferon-related hepatitis B surface antigen seroclearance in genotype D hepatitis B e antigen–negative patients with chronic hepatitis B

Abstract: Interleukin (IL)28B polymorphisms have been associated with interferon (IFN)-induced viral clearance in patients with chronic hepatitis C. Whether this is also true for patients with the difficult-to-cure hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB) is unknown. One hundred and one HBeAg-negative patients (92% genotype D) with compensated CHB (84% males, 46 years; hepatitis B virus [HBV] DNA: 6.0 log cp/ mL; alanine aminotransferase [ALT]: 136 IU/L; 42% with cirrhosis) were followed up for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 35 publications
4
130
4
Order By: Relevance
“…Oddly, this allele was described as a negative predictive factor of PegIFN/RBV efficacy in chronic hepatitis C. Such configuration of alleles, taking into account race differences (more frequent in Caucasians, rare in Japanese and very rare in Chinese Han race) may explain the better response to treatment in chronic hepatitis C caused by genotype 1 in a Far East population, whereas the response to therapy of CHB behaves contrariwise. Lampertico et al [22] analyzed a group of 101 Caucasians infected with HBV genotype D, treated with recombined IFN or PegIFN for an average of 23 months with median follow-up of 11 years. Loss of HBsAg with or without anti-HBs development was considered as the study endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Oddly, this allele was described as a negative predictive factor of PegIFN/RBV efficacy in chronic hepatitis C. Such configuration of alleles, taking into account race differences (more frequent in Caucasians, rare in Japanese and very rare in Chinese Han race) may explain the better response to treatment in chronic hepatitis C caused by genotype 1 in a Far East population, whereas the response to therapy of CHB behaves contrariwise. Lampertico et al [22] analyzed a group of 101 Caucasians infected with HBV genotype D, treated with recombined IFN or PegIFN for an average of 23 months with median follow-up of 11 years. Loss of HBsAg with or without anti-HBs development was considered as the study endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Less favorable results were obtained for patients infected with hepatitis B virus (HBV). Although in some studies, the CC genotype of rs12979860 was an independent predictor of HBsAg seroclearance by interferon therapy, 14 and patients with this genotype were found to have more frequently lower viral load levels, 15 a recent meta-analysis by Tang et al 16 has not found any association between IFNL3 rs12979860 C/T and the risk of persistent HBV infection.…”
Section: 4mentioning
confidence: 98%
“…Probably, the immunomodulatory effect of IFN can persist even after the end of therapy leading to considerable HBsAg clearance rates. In particular, patients carrying ILİstanbul Med J 2017; 18: 189-95 (34). However, these findings are still a subject of debate, since other studies reported no association between treatment outcome or spontaneous HBsAg seroclearance with rs12979860 polymorphism in both HBeAg-positive and -negative CHB patients (35,36).…”
Section: Current Available Drugsmentioning
confidence: 99%